The Impact of Internal Migration on Population Redistribution: an International Comparison - Rees, Philip; Bell, Martin; Kupiszewski, Marek; Kupiszewska, Dorota; Ueffing, Philipp; Bernard, Aude; Charles‐Edwards, Elin; Stillwell, John (Population space and place, 2017)
We know that internal migration shapes human settlement patterns, but few attempts have been made to measure systematically the extent of population redistribution or make comparisons between countries. Robust comparisons are hampered by limited data access, different space‐time frameworks, and inadequate summary statistics. We use new analysis software (IMAGE Studio) to assess the effects of differences in the number and configuration of geographic zones and implement new measures to make comparisons across a large sample of countries, representing 80% of global population. We construct a new Index of Net Migration Impact to measure system‐wide population redistribution and examine the relative contributions of migration intensity and effectiveness to cross‐national variations. We compare spatial patterns using the slope of a regression between migration and population density across zones in each country to indicate the direction and pace of population concentration. We report correlations between measures of population redistribution and national development and propose a general theoretical model suggesting how internal migration redistributes population across settlement systems during the development process. Copyright © 2016 The Authors Population, Space and Place Published by John Wiley & Sons Ltd.